Mavericks at work : why the most original minds in business win - Taylor, William, 1959-; LaBarre, Polly G. (New York : HarperCollins, 2006)
"Business as usual is a bust. In industry after industry, the old guard is cutting back and losing ground. Meanwhile, organizations that were once dismissed as upstarts, as wildcards - or mavericks - are making waves and growing fast. There is a reason: In an age of hypercompetition and nonstop innovation, the only way to stand out from the crowd is to stand for something truly original." "That's the lesson behind the companies, executives, and entrepreneurs you'll meet in Mavericks at Work. They are winning big in business by rethinking the logic of how business gets done. They have devised new answers to the timeless challenges facing organizations of every size and leaders in every field: how you make strategy, how you unleash new ideas, how you connect with customers, how your best people achieve great results."--BOOK JACKET.
Introduction : the maverick promise -- Ch. 1. Not just a company, a cause : strategy as advocacy -- Ch. 2. Competition and its consequences : disruptors, diplomats, and a new way to talk about business -- Ch. 3. Maverick messages (I) : sizing up your strategy -- Ch. 4. Ideas unlimited : why nobody is as smart as everybody -- Ch. 5. Innovation Inc. : open source gets down to business -- Ch. 6. Maverick messages (II) : open-minding your business -- Ch. 7. From selling value to sharing values : overcoming the age of overload -- Ch. 8. Small gestures, big signals : outstanding strategies to stand out from the crowd -- Ch. 9. Maverick messages (III) : building your bond with customers -- Ch. 10. The company you keep : business as if people mattered -- Ch. 11. People and performance : stars, symptoms, and workplaces that work -- Ch. 12. Maverick messages (IV) : practicing your people skills -- App. Maverick material.
Includes bibliographical references.
Keywords: Executives -- United States -- Case studies; Leadership -- United States -- Case studies; Competition -- United States -- Case studies; Success in business -- United States -- Case studies; Competition; Executives; Leadership; Success in business; United States; Case studies; Case studies